A Fuzzy Logic Approach for Improvement of Power Quality Using FC-TCR - Aung, Moh Moh Myint; Oo, Yan Aung (American Scientific Research Journal for Engineering, Technology, and Sciences, 2016)
The reactive power compensation in a power distribution network plays a vital role in improving voltage and power system stability. The increase in the loading of the transmission lines sometimes can lead to voltage collapse due to the shortage of reactive power delivered at the load centers. This is due to the increased consumption of the reactive power in the transmission network and the characteristics of the load. All these problems can be removed by Static Var Compensator (SVC). Fixed capacitor thyristor controlled reactor (FC-TCR) can be used for power factor correction, flicker reduction, and steady-state voltage control, and also have the benefit of being able to filter out harmonics from the system. By changing firing angle of thyristor, voltage profile can be improved up to required level. The performance of FC-TCR with Fuzzy logic controller will be provided by using Matlab/Simulink. The installation site for this proposed system is Zone II Feeder of 132/33/11 kV 30MVA transformer in Tagondaing Substation.